Design of research reporting and data collection information system at public university using design thinking method - Kendry Ayu Laksana; Ika Raharja Salim (Institute of Computer Science (IOCS), 2023)
Current digital developments encourage the world of education to also participate in developing a digitalization environment, especially in higher education. Not only in terms of the learning process, but also in the managerial process, especially in the tridharma business process. This research aims to develop higher education information systems to be more efficient and effective, especially in research business process, namely the process of data reporting and data management. The method used in this research is design thinking, which consists of the empathize, define, ideate, prototype, and testing stages. At the empathize stage, data is collected in the form of strategic plan documents which are then mapped in the form of a business model canvas. Then a user interview is conducted which is then mapped into an empathy map. At the define stage, the results of the interview are detailed in the form of a user persona. From the results of document mapping and user interviews, we enter the ideate stage, namely making user flows and flowcharts. After validating user flow and flowcharts for the user, the prototype stage is carried out, where at this stage Balsamiq 3 tools are used to design the user interface. The results of this study indicate that the designed user interface and flow are in accordance with user needs.